2022
DOI: 10.1101/2022.12.17.520856
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parallels and divergences in landscape genetic and metacommunity patterns in zooplankton inhabiting soda pans

Abstract: Ecological processes maintaining landscape genetic variation and metacommunity structure in natural landscapes have traditionally been studied in isolation. Their integrated study may hold important information as to what extent the effect of major ecological processes are species- or landscape-specific, resulting in a more coherent picture on the spatial organization of biodiversity. Here, we explicitly compared the relative importance of spatial and environmental drivers of both cladoceran metacommunity stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Of these, six clonal lineages from each population were randomly picked out to be used in the common garden experiments, resulting in 21 populations × 6 lineages = 126 lineages. All clonal lineages were expected to be unique clones based on a genetic analysis using 13 microsatellite markers carried out on multiple soda pan and bomb crater pond populations that were sampled in April 2014, where we observed that all individuals differed in multi-locus genotype ([ 47 ]; Z Horváth 2023, personal communication). Based on this, we expect that there were none or only very few genotypes that were represented by two or more individuals.…”
Section: Methodsmentioning
confidence: 99%
“…Of these, six clonal lineages from each population were randomly picked out to be used in the common garden experiments, resulting in 21 populations × 6 lineages = 126 lineages. All clonal lineages were expected to be unique clones based on a genetic analysis using 13 microsatellite markers carried out on multiple soda pan and bomb crater pond populations that were sampled in April 2014, where we observed that all individuals differed in multi-locus genotype ([ 47 ]; Z Horváth 2023, personal communication). Based on this, we expect that there were none or only very few genotypes that were represented by two or more individuals.…”
Section: Methodsmentioning
confidence: 99%
“…Of these, six clonal lineages from each population were randomly picked out to be used in the common garden experiments, resulting in 21 populations x 6 lineages = 126 lineages. All clonal lineages were expected to be unique clones based on a genetic analysis using 13 microsatellite markers carried out on multiple soda pan and bomb crater populations that were sampled in April 2014, where we observed that all individuals differed in multi-locus genotype ( [47]; Horváth Z. pers. comm.).…”
Section: Sampling and Culturing Of D Magnamentioning
confidence: 97%